Growth Performance, Survival Rate and p38 Mitogen-Activated Protein Kinase of Giant Gourami Fry (Osphronemus gouramy) on Different Temperature Levels - Armando, Eric; Tartila, Shobrina Silmi Qori (JURNAL AKUAKULTURA, 2024)
The low survival value of gourami fish juvenile is because gourami is easily stressed. Changes in temperature in the rearing media environment can affect fish life and can even cause stress. Cortisol and blood glucose are indicators of early stress in fish which then naturally respond to the presence of environmental stressors by producing stress proteins such as mitogen-activated protein kinases (MAPKs). The purpose of this study was to analyze changes in growth, survival and p38 MAPKs of gourami fish juvenile reared at different temperatures. The working method used in this research is the experimental method. This research was conducted with 3 treatments and 3 replicates. The treatments given include (A) 27°C temperature treatment, (B) 29°C temperature treatment, (C) 31°C temperature treatment. Observations made were measurements of growth, survival, and p38 MAPK levels as well as physical and chemical parameters. The results of this study indicate that 31°C is the best temperature for gourami, the expression of p38 MAPK shows low distribution characterized by little brown color, survival rate of 80%, length growth of 1.8-2cm and daily growth rate of 0.21 g/day. During the study the pH in the treatments ranged from 7.3-8.1, while oxygen levels ranged from 4.2-7.7mg/l.